PENTINGNYA METODOLOGI PEMBELAJARAN BAGI GURU - M. Ilyas; Abd. Syahid (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
Teacher’s skills in teaching is the process of skill creation based on science and professional, in that process, teacher must carry out a sustainable and structured learning in line to his or her lesson planin order to achieve the desired goals both student and teacher. By definition, methodology of teachingis the way used by teachersto establish the relationships with student during the learning.